Market Potential Exploration of Tourism Sector and Local Tourists’ Perception - Nanang Wahyudin; Sandy Pratama; Muhammad Faisal Akbar (Integrated Journal of Business and Economics (IJBE), 2019)
This research discussed domestic tourists' perception of tourism destination in Pangkalpinang, Indonesia. It has been formed a perception index using PCA with determined indicators such as accessibility, supporting facilities, the prices of snacks and security. The result indicates that most of the visitors have good perceptions of tourism destinations in Pangkalpinang. Nevertheless, there is an aspect that should be evaluated; it is about the availability of toilets at those tourist destinations. There is 53 percent of domestic tourists tell that there is no access to public toilet. Therefore, this research describes stakeholder to understand the existing condition and make an improvement in the future.